The Grandeur of Indonesian Culture: Analyzing Audience Responses to Indonesia’s Cultural Showcase at the G20 Gala - Prida Ariani Ambar Astuti; Laila Mahrid (Scriptura, 2025)
This study analyzes audience perceptions of the Cultural Performance G20 broadcast on Kompas TV’s YouTube channel as a medium for transmitting Indonesia’s cultural diversity values. Employing a quantitative approach with a descriptive survey method, the research involved 100 respondents who are subscribers of Kompas TV on YouTube. The findings reveal that viewers have a positive perception of the broadcast, particularly on the cultural voice-over, which effectively highlights the richness of Indonesian culture. The results indicate that creatively packaged audio-visual content with strong narratives, visuals, and high-quality audio can enhance audience appreciation of cultural diversity. Based on the Uses and Gratification theory, the broadcast fulfills audience needs for information, entertainment, and personal identity, especially among Generation Z, which dominates the respondents.